Fractais: generalização de padrões no ensino fundamental - Mineli, Juliano de Paula (2012)
This research aimed to study the formation of skills of elementary school students to solve problems, or more specifically, problems whose solutions can be expressed by 1st order equations. My teaching experience has made me raise a hypothesis that the difficulties that students encountered in the organization of the equation, related to the situations of Generalization of Patterns. From then define the objectives of this research is to: investigate problems related to skills training for the Generalization of Patterns and teaching situations to facilitate the training. For data collection, drafted a sequence containing three Curriculum Activities supported on the elements of Fractal Geometry, with a view to generalization of Standards and their implementation based on the Theory of Didactic Situations of Brousseau - theoretical framework used in this research.This sequence was applied in seven sessions to a class of 7th grade (6th grade) of a private Institution located in the city of Ribeirão Preto.This is a qualitative research study using a methodology supported by the Didactic Engineering. The observations and analyzes showed that: the characteristics of fractal figures provide pattern recognition, pattern recognition encourages students to make generalization, the use of geometric shapes provides better organization of data from a mathematical problem, which favors their resolution; generalization of a given situation helps the development of algebraic thinking as well as their attitudes and autonomy in order to observe, raising conjectures, draw conclusions and justify their answers